PELATIHAN PERAWATAN LUKA PADA KADER DI KELURAHAN KEPATIHAN KULON JEBRES SURAKARTA - Hermawati Hermawati; Ika Silvitasari (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Background: The incidence of injuries is increasing every year, both acute and chronic wounds. A recent study in America showed the prevalence of patients with wounds was 3.5% per 1000 population. This requires wound care materials that must be adapted to the characteristics of the patient's wound. It is hoped that by increasing the understanding and skills of cadres, families can carry out wound care at home. Targets and outputs: dasa wisma cadres and dasa wisma members in Kepatihan Kulon Jebres Village, Surakarta. The benefit of this activity is to increase knowledge and change the attitude of the dasa wisma cadres in wound care training. The output of this activity is skills on how to treat wounds and know the signs of infection in wounds. Implementation method: lectures, simulations and demonstrations. Results and Conclusions: Wounds with any condition must be treated properly so as not to cause infection to cause amputation. One of those who play a role in this is the family. The results of the evaluation in the last week showed that the wound was regenerating.Â Keywords ;Training; injury cure; Cadre